Ionization Efficiency in a Hot Flat Disc-Shaped Cavity - M. Turek (Приборы и методы измерений, 2020)
Hot cavity ion sources of different kinds are widely used in nuclear and mass spectroscopy, especially in on-line isotope separation devices attracting attention of scientists and engineers looking for high ionization efficiency, robustness and beam purity. In the paper a new type of hot ionizer cavity is proposed: namely cavity having the shape of a flat disc, which may be especially suitable for short-lived nuclides to be ionized.A numerical model of the ion source is presented in the paper. The particle tracking code takes into account ionization at hot surfaces and enables modeling of both flat disc cavity and standard elongated cavity ionizers. The code enables calculation of total ionization efficiency and is suitable for stable and long-lived nuclides.Influence of the flat disc cavity geometry (thickness and radius) and its temperature on total ionization efficiency was considered – it was shown that the efficiency increases with cavity radius due to the growing number of particle-wall collisions. This effect may be important in the case of the hard-to-ionize nuclides.The optimal ionizer geometry is characterized by 90 % efficiency, even for substances with rather low ionization coefficient (of order 0.05). The role played by the size of the extraction opening is explained – it is demonstrated that the ionization efficiency increases due to the opening radius reduction. It is also proven that extraction voltage of 1–2 kV is sufficient to maintain optimal ionizer efficiency.